Experimental Study on Seismic Behavior of Composite Shear Wall with Inclined Bars - Y. L. Wang (Hindawi Limited, 2021)
The composite shear wall is the core component of the thermal insulation integrated structure, which is a load-bearing shear wall with good thermal insulation, sound insulation, and seismic resistance. To improve the applicable height of the composite shear wall structure, a cohesive sandwich heat-insulation composite shear wall with door frame inclined tendon and diamond-shaped inclined tendon is proposed, and the quasistatic force of four 1/2-scale shear wall test specimens is carried out. Different specimens are analyzed, including failure modes, hysteresis curves, skeleton curves, stiffness degradation, ductility performance, and energy dissipation capacity. The following conclusions are drawn: the failure modes of the specimens are bending and shear failure; the ultimate strength and deformation performance of the composite wall close to the solid wall; the composite wall with the door frame inclined tendon can effectively delay the wall cracking and improve the bearing capacity and energy consumption capacity of the composite wall; the configuration of the diamond-shaped inclined tendon improves the ductility and energy dissipation capacity of the composite wall.